Do carnitine and extra trace elements change stability of paediatric parenteral nutrition admixtures?. Issue 5 (October 2019) - Forchielli, M.L.; Bonoli, A.; Stancari, A.; Bruno, L.L.; Piro, F.; Piazza, G.; Albertini, C.; Pession, A.; Puggioli, C.; Bersani, G.
Summary: Introduction: High concentrations of trace elements (TE), in particular zinc and selenium, along with carnitine, are often added to parenteral admixtures in paediatric patients on long-term Parenteral Nutrition (PN). We aim to evaluate whether lipid droplet diameters of these admixtures maintain the recommended range of 0.4–1.0 μm. Materials and methods: Stability studies were carried out on six parenteral admixtures with carnitine, trace elements and electrolytes added in different amounts. Each admixture was formulated with five different lipid emulsions with or without fish oil. Analyses were performed at time 0 (t = 0) and 24, 48, 72, 96 (t = 96) hours after compounding. Droplet diameters were determined by Light Scattering-Reverse Fourier Optics Technique. Samples, stored at 4 °C, were triple tested for a total of 450 analyses. Regression analyses were performed using panel-data techniques. Results: During the 4 days, lipid droplet diameters were in the expected range of 0.4–1.0 μm regardless of trace element and carnitine amounts in all admixtures apart from those containing fish-oil based emulsions and calcium concentrations equal to 4.5 mmol/L. In these latter admixtures, 12% of droplet diameters were larger than 1.0 μm and 2% exceeded 5.0 μm immediately after compounding. Conclusion: Carnitine and high concentrations of trace elements do not affect PN admixtures stability and can be safely infused in long-term home-PN paediatric patients and prematures. Only high calcium concentrations in compresence with fish oil based lipid emulsions seem to change PN stability.